1998
DOI: 10.1097/00002030-199816000-00013
|View full text |Cite
|
Sign up to set email alerts
|

The impact of HIV on Streptococcus pneumoniae bacteraemia in a South African population

Abstract: The burden of bacteraemia due to S. pneumoniae in HIV-seropositive individuals admitted to our hospital is considerable. Differences in the S. pneumoniae serotypes/serogroups in HIV-infected patients have been demonstrated with resultant differences in antibiotic susceptibility patterns. Excellent potential for vaccine coverage was demonstrated for both HIV-seronegative and HIV-seropositive individuals. Further studies are necessary to test the clinical efficacy of pneumococcal vaccination of HIV-seropositive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 11 publications
2
60
0
5
Order By: Relevance
“…Отдельного внимания заслуживает инвазивная пневмококковая инфекция (ИПИ), которая более чем в 80 % наблюдений протекает с поражением лег ких и является одной из основных причиной смерти среди ВИЧ инфицированных пациентов [35][36][37][38]. В период до АРВТ пневмококковая бактериемия ре гистрировалась у ВИЧ инфицированных более чем в 100 раз чаще, чем у людей без ВИЧ [39].…”
Section: клиническая картина диагностика и прогноз вп у лжвunclassified
“…Отдельного внимания заслуживает инвазивная пневмококковая инфекция (ИПИ), которая более чем в 80 % наблюдений протекает с поражением лег ких и является одной из основных причиной смерти среди ВИЧ инфицированных пациентов [35][36][37][38]. В период до АРВТ пневмококковая бактериемия ре гистрировалась у ВИЧ инфицированных более чем в 100 раз чаще, чем у людей без ВИЧ [39].…”
Section: клиническая картина диагностика и прогноз вп у лжвunclassified
“…La infección por el virus de la inmunodeficiencia humana, la formación defectuosa de anticuerpos congénita o adquirida, la neutropenia, la asplenia anatómica o funcional, los linfomas, la insuficiencia renal crónica, el síndrome nefróti-co y los transplantes de órganos son factores que aumentan la susceptibilidad debido a la depresión inmunológica que ocasionan [40][41][42] . Otros factores predisponentes son: el tratamiento con corticoides, la desnutrición, la cirrosis hepática, la diabetes mellitus, el alcoholismo, la enfermedad cardiovascular crónica, la hospitalización, la fatiga, el estrés, la exposición al frío y las infecciones víricas respiratorias.…”
Section: Susceptibilidadunclassified
“…5 Rates of IPD amongst HIV-seronegative adults over 65 years of age in a South African study were found to be 64 per 100,000. 6 However, this picture is likely to worsen in the near future due to the growing impact of HIV/AIDS, as the same study found IPD rates of 197 per 100,000 in HIV-seropositive adults aged 18-40 years. 6 The primary difference between the developed and the developing world in the case of pneumococcal infection is that of mortality.…”
mentioning
confidence: 99%
“…6 However, this picture is likely to worsen in the near future due to the growing impact of HIV/AIDS, as the same study found IPD rates of 197 per 100,000 in HIV-seropositive adults aged 18-40 years. 6 The primary difference between the developed and the developing world in the case of pneumococcal infection is that of mortality. 5 Mortality rates in the developing world greatly exceed those in the developed world; the results of a vaccine efficacy study in Papua New Guinea suggested that pneumococcal disease may have previously been responsible for 21% of all deaths in the area.…”
mentioning
confidence: 99%